Characterisation of HIV superinfection : genetic evolution and adaptive immune responses - Harvey, Hayley Janet (Division of Virology, 2014)
In this thesis we aimed to determine the timing and frequency of intra-subtype C superinfection, and to determine if the reason for superinfection was a greater genetic distance within epitopes of the superinfecting virus compared to those of circulating strains from the same cohort.